DEVELOPING STUDENTS’ CREATIVE THINKING THROUGH INNOVATIVE MULTIMEDIA TECHNOLOGIES - Khalikova Latofat Oktamovna (Bright Mind Publishing, 2026)
This article analyzes the issues of developing students’ creative thinking through the use of innovative multimedia technologies in the modern educational process. The study examines the pedagogical essence of the concept of creative thinking, the didactic potential of multimedia tools in its formation, and effective methods for organizing creative education. In addition, the paper substantiates interactive methods and practical approaches that contribute to the development of students’ creative thinking abilities within a digital learning environment.
Keywords: Creative thinking, multimedia technologies, innovative education, creative pedagogy, interactive learning, digital learning environment.